Perancangan Sistem Informasi Perpustakaan Berbasis Website di SMP Negeri 1 Anjatan - Annisa Nur Ashila; Dian Pemata Sari; Suprih Widodo (Jurnal Informatika, 2024)
SMP Negeri 1 Anjatan is a junior high school located in Anjatan Indramayu Regency. To make it easier for Library Officers to manage libraries, a library information system is needed. the Information System created includes: attendance visits, management of borrowing and returning books, and the process of managing book collections.An information system is a collection of elements interconnected with each other that form a single whole for integrating data, processing and storing and distributing information. Library Information System is a system that exists in an organization that meets the needs of daily data processing, supporting activities in data storage, and providing certain outside parties with the necessary reports. The method used in the development of this library information system using SDLC with RAD model. Stages in the RAD method are requirement planning, user design, constructions, and cutover. Making this information system using PHP Programming Language, HTML, CSS. Using Visual Studio Code as note editor, in the implementation of data base using local server from MySQL.Questionnaires that will be used for prototype testers at the user design stage and the results of contructions are SUS (System Usability Scale) and blackbox testing. Where SUS to measure the Usability of Information Systems and use Black box testing to measure functional suitability.The results of SUS prototype testing included in the good category and acceptability ranges included in the acceptable category. The results of black box testing, all questions on the questionnaire were successful, which means the score of the black box testing is 100%. Based on testing, the Library Information System can be said to be feasible to use.